“The Ecopoetics of Magic: Joy Harjo’s Universal and Dreamy Places” - Mancelos, João de (2017)
Joy Harjo is one of the most prominent Native American poets of her generation. In my paper, I classify and analyze the different types of space that emerge in her poetry: a) places of communication with the universe; b) places that can only be visited in dreams; c) places of origin. My objective is to draw attention to the spiritual and aesthetic importance of these spaces, and search for patterns and reconfigured myths. I include quotations from her poems and excerpts from an unpublished interview Harjo gave me in June 2001.